2016
DOI: 10.1016/j.ica.2016.02.053
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding, topoisomerase inhibition and cytotoxicity of palladium(II) complexes with 1,10-phenanthroline and thioureas

Abstract: Metallointercalators represent a promising alternative in cancer chemotherapy. We present herein DNA binding, topoisomerase inhibition and cytotoxic studies on a series of complexes of general formulae [Pd (phen)(tu ⁄) 2 ] 2+ incorporating the intercalator 1,10-phenanthroline and thiourea ligands (L = thiourea 1, N-methylthiourea 2, N,N 0-dimethylthiourea 3). DNA-unwinding results showed that the complexes can induce the unwinding of the plasmid DNA. The binding constants (K b) for the interaction of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 62 publications
0
19
0
2
Order By: Relevance
“…In this regard, we have previously shown that bipyridyl complexes of Pt(II) with thiourea are able to inhibit TOPO-II activity [9] and, more recently, Barra et al showed that three Pd(phen) complexes, including our [Pd(phen)tu 2 ]Cl 2 and [Pd(phen)(Me-tu) 2 ]Cl 2 , were also active as TOPO-II inhibitors in a dose-dependent manner [14]. We confirmed here that metal phenanthroline complexes were active TOPO-II inhibitors, and showed again that Pd(phen) were the most active TOPO-II inhibitors among the tested metal planar complexes, even at the smallest concentration tested.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In this regard, we have previously shown that bipyridyl complexes of Pt(II) with thiourea are able to inhibit TOPO-II activity [9] and, more recently, Barra et al showed that three Pd(phen) complexes, including our [Pd(phen)tu 2 ]Cl 2 and [Pd(phen)(Me-tu) 2 ]Cl 2 , were also active as TOPO-II inhibitors in a dose-dependent manner [14]. We confirmed here that metal phenanthroline complexes were active TOPO-II inhibitors, and showed again that Pd(phen) were the most active TOPO-II inhibitors among the tested metal planar complexes, even at the smallest concentration tested.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that both AT and GC base pairs may stably bind the phenanthroline ligand, but its affinity is larger for the GC base pair [29]. In this regard, some Pd(phen) compounds, including our [Pd(phen)tu 2 ]Cl 2 and [Pd(phen)(Me-tu) 2 ]Cl 2 , have been suggested to form hydrogen bonds with guanosine [14]. Therefore, our complexes bearing the phenanthroline moiety, in particular those with Pd(II), are likely powerful nucleic acid inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by the aforementioned observations, and as a part of our continuing research program in the field of coordination and biological chemistry of metal complexes [12][13][14][15][16][17][18][19], we present herein the synthesis and characterization of the complexes cis-[PdX 2 (imzt)(PPh 3 )] {imzt = imidazolidine-2-thione; PPh 3 = triphenylphosphine; X = Cl (1), Br (2), I (3), SCN (4)}, together with the effect of complexes 1-4 on the viability of U87MG human glioma cells.…”
Section: Introductionmentioning
confidence: 99%